IMPLEMENTASI MATA KULIAH PENDIDIKAN INKLUSI BAGI MAHASISWA PGSD - Anggita Tampubolon, Rina; Indah Wahyuningsih, Putri; Munfariqoh, Aqidatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to explain in detail the implementation of inclusive education courses, especially for PGSD UPGRI Palembang students. The method used is descriptive qualitative with the research objects being PGSD students. Data collection techniques were carried out through questionnaires, interviews and document collection. Research findings show that there are several supporting factors, including students feeling that inclusive education courses are very important as preparation for becoming elementary school teachers. Apart from that, students also realize that inclusive education is an approach that is fair, equal and respects diversity. Varied methods, classrooms equipped with projectors, internet facilities and adequate electricity, interactive quizzes using google form help students evaluate the learning process. Inhibiting factors for analyzing inclusive education material through discussion activities and actively participating in question and answer sessions. The findings of this research show that student motivation, active participation, and available infrastructure need to be maintained and improved. As a result, inclusive education in higher education institutions can be used as a course that prepares prospective teachers to face various types of diversity in elementary schools.